Investigating the Sensitivity of Nasal or Throat Swabs: Combination of Both Swabs Increases the Sensitivity of SARS-CoV-2 Rapid Antigen Tests - Barbara L. Goodall; Jason J. LeBlanc; Todd F. Hatchette; Lisa Barrett; Glenn Patriquin (Microbiology Spectrum, 2022)
ABSTRACT The COVID-19 pandemic has been hallmarked by several waves of variants of concern (VoCs), each with novel challenges. Currently, the highly transmissible Omicron VoC is predominant worldwide, and sore throat is common, among other cold-like symptoms. Anecdotes on social media have suggested that sampling one’s throat can increase the sensitivity for Omicron detection by antigen-based rapid testing devices (Ag-RDTs). This work aimed to improve the local testing strategy and determine whether the sensitivity of Ag-RDTs designed for nasal sampling is altered with the use of self-administered throat swabs in self-perceived asymptomatic individuals. This investigation used a common Ag-RDT (i.e., Abbott Panbio COVID-19 Ag rapid test device) to compare three sampling sites: nasal swab, throat swab, and combined nasal/throat. All Ag-RDT results were confirmed with molecular testing from residual test buffer. Compared to reverse transcriptase PCR (RT-PCR), samples from nasal or throat swabs each detected 64.5% of SARS-CoV-2 cases; however, combining the contributions of each swab increased the positive percent agreement (PPA) with RT-PCR to 88.7%. This trend was also evident with the Rapid Response Ag-RDT (BTNX), which uses more flexible swabs than does the Panbio. When nasal swab collection was compared to paired sampling of the nose/throat using a single swab with the Panbio Ag-RDT, the PPAs were 68.4% and 81.6%, respectively. No false-positive results were observed with nasal, throat, or combined nasal/throat sampling. Self-administered throat and nasal/throat swabs both had >90% acceptability. These findings support the use of self-collected combined nasal/throat sampling for Ag-RDT-based SARS-CoV-2 detection in self-perceived asymptomatic individuals. IMPORTANCE This quality project demonstrates that combining the results of nasal and throat swabs or using a combined single swab of the throat and nares resulted in increased detection of SARS-CoV-2 using a rapid antigen test, in an asymptomatic population. Importantly, no false positives were detected, and over 90% of people were willing to perform the combination swab. These types of projects are instrumental in informing local practices to improve testing strategies. These data support the option of using a combined nasal/throat swab in our local setting to enhance the detection of Omicron.